A 3D plant layout model considering pipeline route arrangement. (1st January 2014) - Ohmori, Shunichi; Nono, Yuki; Yoshimoto, Kazuho
We have developed a three-dimensional plant layout model considering I/O points and pipeline route arrangement. It is known that the much of operating costs in a typical industrial plant can be attributed to layout and pipeline design, and thus, the computer-aided layout has been studied to help layout planners consider various alternatives in a very short time. In this paper, we proposed a two-phase method: layout arrangement and pipeline arrangement. In the layout arrangement, we use continuous representation model for simplicity and accuracy, using MIP-based formulation. We apply particle swarm optimisation (PSO) to get a preferred set of relative-positioning of equipments quickly. We then optimise the layout arrangement under the specified relative-positioning. In the pipeline arrangement, we cast the plant layout into the graph representation. To cast layout representation, we propose graph creation technique called '3D min-max method' that enables us to project nodes and arcs onto the obtained layout. We then set the pipeline route onto the shortest path between equipment, using Dijkstra's method. In the numerical experiments, we show how our method can be applied to industrial application.